Asexuality vs. sexual interest/arousal disorder: Examining group differences in initial attention to sexual stimuli - Bradshaw, Julia; Brown, Natalie; Kingstone, Alan; Brotto, Lori (PLOS ONE, 2021)
Attention is considered to be a critical part of the sexual response cycle, and researchers have differentiated between the roles of initial (involuntary) and subsequent (voluntary) attention paid to sexual stimuli as part of the facilitation of sexual arousal. Prior studies using eye-tracking methodologies have shown differing initial attention patterns to erotic stimuli between men and women, as well as between individuals of different sexual orientations. No study has directly compared initial attention to sexual stimuli in asexual individuals, defined by their lack of sexual attraction, to women with Sexual Interest/Arousal Disorder (SIAD), a disorder characterized by a reduced or absent interest in sex coupled with significant personal distress. The current study tested differences in the initial attention patterns of 29 asexual individuals (Mage = 26.56, SD = 4.80) and 25 heterosexual women with SIAD (Mage = 27.52, SD = 4.87), using eye-tracking. Participants were presented with sexual and neutral stimuli, and their initial eye movements and initial fixations to both image types and areas of erotic contact within sexual images were recorded. Mixed-model ANOVAs and t-tests were used to compare the two groups on the speed with which their initial fixations occurred, the duration of their initial fixations, and the proportion of initial fixations made to sexual stimuli. On two indices of initial attention, women with SIAD displayed an initial attention preference for sexual stimuli over neutral stimuli compared to asexual participants. This study adds to a growing literature on the distinction between asexuality and SIAD, indicating that differences in early attention may be a feature that differentiates the groups.